Estimating risk premia in money market rates - Rasmus Pilegaard; Alain Durré; Snorre Evjen (European Central Bank (ECB), 2003)
This paper empirically tests the expectations hypothesis on both daily EONIA swap rates and monthly EURIBOR rates extended backwards with German LIBOR rates. In addition, we quantify the size of the risk premia in the money market at maturities of one, three, six and nine months. Using implied forward and spot rates in a cointegrated VAR model, we find that the data support the expectations hypothesis in the euro area and in Germany prior to 1999. We find that risk premia are relatively limited at the shorter maturities but more significant at maturities of six and nine months. Furthermore, the results on LIBOR/EURIBOR rates tentatively indicate a downward shift in the structure of the risk premia after the introduction of the euro.
Keywords: E43; C32; 330